Reconstructing Presidential Legislative Authority: Analyzing the System and Strengthening Modern Democracy - Rismawati Nur (PDIH Untag Semarang, 2025)
This study aims to reconstruct the President’s legislative authority within Indonesia’sconstitutional framework by reformulating Article 20 of the 1945 Constitution toalign with the principles of modern presidentialism. The research employs a normativejuridical method using conceptual, statutory, and comparative constitutionalapproaches. Comparative analyses are conducted with the presidential systems of theUnited States and Brazil to identify an institutional design that ensures an effectiveseparation of powers and strengthens checks and balances. The findings indicate thatlimiting the President’s legislative authority by transferring deliberative functionsentirely to the House of Representatives, while maintaining the President’s role inbudget initiation and administrative assent, establishes a more accountable andbalanced governance system. This model enhances public participation, ensureslegislative transparency, and reinforces democratic legitimacy through the absolutemajority voting principle and automatic approval mechanism. The study suggests thatconstitutional amendments should clearly separate executive and legislative powersand institutionalize public involvement in lawmaking to prevent executive dominance.Strengthening legislative independence through these reforms will promote a moreparticipatory and responsive democratic system consistent with the rule of law and theprinciples of modern constitutional democracy.